2019
DOI: 10.3390/nu11092000
|View full text |Cite
|
Sign up to set email alerts
|

Association of Low Serum l-Carnitine Levels with Peripheral Arterial Stiffness in Patients Who Undergo Kidney Transplantation

Abstract: l-carnitine is an important co-factor in fatty-acid metabolism, and its deficiency is associated with insulin resistance, which is independently associated with arterial stiffness. This study evaluated the relationship between serum l-carnitine level and peripheral arterial stiffness (PAS) in kidney transplantation (KT). Fasting blood samples were collected from 65 patients who underwent KT. We measured the brachial–ankle pulse wave velocity, and 36 patients (55.4%) had PAS. Patients with PAS had a significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…All the samples were stored at −80 °C and the storage time was less than one year. The plasma levels of fasting blood glucose (Glu-AC) and lipid profiles (TG, TCH, HDL-C, and LDL-C) were determined using the COBAS Integra 800 autoanalyzer (Roche Diagnostics, Basel, Switzerland) [ 25 , 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…All the samples were stored at −80 °C and the storage time was less than one year. The plasma levels of fasting blood glucose (Glu-AC) and lipid profiles (TG, TCH, HDL-C, and LDL-C) were determined using the COBAS Integra 800 autoanalyzer (Roche Diagnostics, Basel, Switzerland) [ 25 , 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…Previous reports have shown baPWV values are positively correlated with high-sensitivity CRP in the 45-54 years group and in a male Japanese population [31,32]. In our previous reports, PAS was associated with higher SBP, higher percentage of DM, serum insulin levels, and homeostasis model assessment of insulin resistance in patients who underwent kidney transplantation [20,33]. The positive correlation between SBP, DMlog-CRP, and baPWV values, while negative correlation between eGFR and baPWV values was also showed in our patients with CAD.…”
Section: Discussionmentioning
confidence: 70%
“…Likewise, Higuchi et al [ 16 ] reported that administration of LC supplements had a beneficial effect with respect to decreased brachial-ankle PWV; these findings highlighted its anti-atherosclerotic effects in HD patients with carnitine deficiency. Finally, Lai et al [ 12 ] recently reported the negative relationship between brachial-ankle PWV and serum LC levels in renal transplantation recipients. In view of these findings and together with our study, the negative association between serum LC levels and cfPWV may be the result of inflammation, oxidative stress, and/or endothelial dysfunction, although a precise and detailed mechanism would require further evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…The retention time for free LC was determined at 2.49 min. Quantification of the endogenous compounds was performed by measuring peak areas, followed by comparison to a calibration curve of the standard solutions [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation